Investigation of Sports-Trained Students’ Eating Habits according to Some Parameters Before and During the Coronavirus Outbreak - Yildirim, Yunus; Muftuoglu, Necla Ezgi; Imamoglu, Osman (Progress in Nutrition, 2021)
Study Objectives: The aim of this study was to investigate the eating habits of university sports trained students according to some parameters during the coronavirus pandemic. Methods: The questionnaires filled out by a total of 333 students studying at Mersin University Faculty of Sport Sciences were evaluated. Independent t-test, paired t-test, one-way variance analysis, and LSD tests were used in statistical processes (p>0.05). Results: Students’ pre-pandemic eating habits scores are significantly lower than those of the pandemic eating habits (p<0.001). The difference between the scores of students who made changes in nutrition and those who did not change was found statistically significant (p<0.05). The difference in nutritional habits scores according to the team and individual sports status is statistically insignificant (p>0.05). During the pandemic process, the nutritional habits scores significantly changed according to whether or not students skip meals and the number of daily meals (p<0.05). Again, nutritional habit scores vary significantly depending on the state of use of supplements (p<0.001). Watching television and following coronavirus news on the internet exposure to coronavirus news in social media has been shown to affect eating habits (p<0.01). Conclusion: During the coronavirus pandemic, it was determined that there was little change in the nutritional habits of students who received sports training at the university. Students’ eating habits are at moderate risk. The risk level of eating habits decreased in those who used supplements in their diet. Sports-trained students ’ eating habits were similar according to gender, team and individual sports status, while daily skipping meals, the number of meals eaten daily, the state of use of supplement products, monitoring news of the coronavirus on social media, and exposure were observed to vary according to the state.